2021
DOI: 10.1108/jmtm-01-2021-0026
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0 technologies usage: motives and enablers

Abstract: PurposeThe paper aims to contribute to a better understanding of the drivers for the use of Industry 4.0 technologies by investigating (1) what motivates companies to consider using I4 technologies and (2) what enables (or hinders) the intention to use I4 technologies to translate into their actual use.Design/methodology/approachThe study uses survey data collected from a sample of export-oriented manufacturing companies with more than 10 employees. Final analysis is conducted on 124 companies.FindingsThe resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…Thus, such technology allows companies to synthesize cost innovations from the received data. There are studies that investigated motivations for developing technological organizations, the results of which found that the main motivations are cost reduction and quality, speed, and efficiency improvement [14,41]. The results of this study prove that being a technological organization facilitates cost innovation management.…”
Section: -4-structural Model and Hypotheses Testingmentioning
confidence: 55%
See 2 more Smart Citations
“…Thus, such technology allows companies to synthesize cost innovations from the received data. There are studies that investigated motivations for developing technological organizations, the results of which found that the main motivations are cost reduction and quality, speed, and efficiency improvement [14,41]. The results of this study prove that being a technological organization facilitates cost innovation management.…”
Section: -4-structural Model and Hypotheses Testingmentioning
confidence: 55%
“…An empirical study of the motivation to evolve into a technology organization significantly depends on intra-organizational motivation to increase operational efficiency and competitive advantage. The result does not find the influence of external motivation, such as competitors, suppliers, and customer pressure [14].…”
Section: -1-technological Organizationmentioning
confidence: 80%
See 1 more Smart Citation
“…Today's manufacturing business must adapt to an increasingly dynamic environment and various developments in order to fulfill market expectations. Product life cycles are becoming shorter, production batches are becoming smaller, and dynamic product variations are coupled with growing complexity, all of which pose difficulties to traditional manufacturing processes [129,130]. Thus, traditional manufacturing plants have been compelled to evolve into smart factories equipped with Industry 4.0 enabling technologies [131].…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Furthermore, the reasons for introduction are different. In the literature, is stated how the intentions to use Industry 4.0 technologies are more influenced by the expected increase in efficiency than by pressures from suppliers, customers, or even competitors [126]. On the other side, other results yield that the market uncertainty of the business is a significant driver for adoption of Industry 4.0 technologies [127].…”
mentioning
confidence: 99%